Neuroticism and stress: the role of displacement behavior - Mohiyeddini, Changiz; Bauer, Stephanie; Semple, Stuart (Anxiety, stress, and coping, 2015)
Background and Objectives: Neuroticism is linked with an impaired ability to cope with stress and is an important risk factor for stress-related disorders. Hence, there is interest in exploring the behavioral correlates of neuroticism and how such behaviors may moderate the link between neuroticism and the response to stress. Displacement behavior - activity such as face touching and scratching - is important to investigate in this respect, as recent studies indicate that such behavior is linked to negative emotional states and has an important stress coping function. Here, we explored the relationship between neuroticism, displacement behavior, and stress in a healthy population of men. Design: This was a cross-sectional, quasiexperimentally controlled study. Methods: We assessed participants' levels of neuroticism, and then during a Trier Social Stress Test quantified displacement behavior, physiological, and cognitive indices of the stress response; after the test we measured the self-reported experience of stress. Results: Displacement behavior was negatively correlated with self-reported experience, physiological, and cognitive measures of stress and moderated the relationships between neuroticism, self-reported experience, and cognitive index of stress. Conclusions: Our results suggest displacement behavior plays an important role in shaping the link between neuroticism and the response to stress.
Accepted author version posted online: 19 Jan 2015
Gesehen am 08.06.2020